The new chips on the block [network processors]. - Geppert, L.
The author describes how rapidly expanding network applications and soaring performance requirements need flexible microprocessor solutions that are powerful enough to handle ever-growing data traffic
Keywords: Data traffic; Flexible microprocessor solutions; Microprocessors; Network applications; Network processors; Performance requirements